The development of an online measure of therapist competence. - Cooper, Z; Doll, H; Bailey-Straebler, S; Kluczniok, D; Murphy, R; O'Connor, M; Fairburn, C (Elsevier, 2015)
The topic of therapist training has been relatively neglected in the research literature. Similarly, the related issue of the measurement of the outcome of training, especially therapist competence, has been largely overlooked. Data supporting the effectiveness of various methods of clinician training and those providing estimates of the level of competence achieved by clinicians are scarce. Validated scalable methods for the measurement of clinician outcomes such as competence are required to evaluate both existing and new methods of training. This study focuses on the development and testing of an online measure (eMeasure) to assess therapists' applied knowledge of Enhanced Cognitive Behaviour Therapy (CBT-E), a transdiagnostic evidence-supported treatment for the full range of eating disorders. The eMeasure meets the stringent requirements of the Rasch model and has three equivalent versions making it suitable for repeat testing of trainees in outcome studies. Preliminary best cut points to distinguish between those who are competent and those who are not are identified. While the present work focused on CBT-E, the method described may be used to develop and test other measures relating to therapist competence.